Propagation strategies of Deyeuxia angustifolia in heterogeneous habitats - Dong, Haipeng; Xie, Lihong; Cao, Hongjie; Zhang, Yu; Liu, Yingnan; Xing, Junhui; Fu, Xiaoling; Wang, Jianbo; Han, Dayong; Zhong, Haixiu; Luo, Chunyu; Qu, Yi; et al. (Frontiers in Ecology and Evolution, 2023)
Plants utilize different strategies in different environments to maximize population expansion. Understanding plant reproductive strategies in heterogeneous habitats is therefore important for explaining plant ecological adaptability, and for effectively managing and conserving ecosystems. We wanted to explore the reproductive strategy transformation of D. angustifolia in heterogeneous habitats, as well as the environmental factors driving and affecting its reproductive characteristics. To do this we measured the reproductive characteristics of D. angustifolia, as well as the soil physical and chemical properties of these heterogeneous habitats. The density, biomass per unit area, and proportion of aboveground biomass in swampy meadows were significantly higher compared to other habitats. The proportion of rhizome node buds gradually increased from swampy to typical to miscellaneous grass meadows, while the proportion of tillering node buds decreased. The allocation of sexual reproduction within D. angustifolia populations was significantly and positively correlated with plant rhizome biomass and negatively correlated with the number of tillering node buds. The propagation strategies of D. angustifolia in heterogeneous habitats were consistent with CSR theory (Competitor, Stress-tolerator, and Ruderal). The proportions of inflorescence and rootbiomass in miscellaneous and typical meadows were high, which tended towards the "Ruderal" adaptation strategy. In swampy meadow, D. angustifolia invested mostly in vegetative growth to produce tiller node buds and ramets, which is characteristic of the “Competitor” strategy. Swamp D. angustifolia resisted flooding by maintaining a resource balance in its body, and was therefore biased towards the “Stress-tolerator” strategy. Environmental factors accounted for 74.63% of reproductive characteristic variation, in which the interpretative proportions of soil water content, dissolved organic carbon, ammonia nitrogen, and nitrate nitrogen were significant. When soil water content, dissolved organic carbon, and nitrate nitrogen increased, D. angustifolia tended towards the C strategy; in contrast, when soil water content decreased, amine nitrogen and available phosphorus increased, and D. angustifolia tended towards the R strategy. In a stressful environment, the escape mechanism constitutes an increased rhizome and sexual reproduction investment. For suitable habitats, tillering node buds increased in order to expand the population via new plant production, which was the propagation strategy of D. angustifolia in heterogeneous habitats.